The son of Neptune - Riordan, Rick (New York Disney/Hyperion Books, 2011)
Demigod Percy Jackson, still with no memory, and his new friends from Camp Jupiter, Hazel and Frank, go on a quest to free Death, but their bigger task is to unite the Greek and Roman camps so that the Prophecy of Seven can be fulfilled
1 14
NEW, LITERATURE
Keywords: Mythology, Greek -- Juvenile fiction; Mythology, Roman -- Juvenile fiction; Camps -- Fiction; Gaia (Greek deity) -- Fiction; Hera (Greek deity) -- Fiction; Monsters -- Fiction; Mythology, Greek -- Fiction; Mythology, Roman -- Fiction; Prophecies -- Fiction